2020
DOI: 10.3390/antiox9060460
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine and NAD+ Improve Motor Neural Integrity of Dissociated Wobbler Cells In Vitro

Abstract: Amyotrophic lateral sclerosis (ALS) is a common degenerative disease of the central nervous system concerning a progressive loss of upper and lower motor neurons. While 5%–10% of patients are diagnosed with the inherited form of the disease, the vast majority of patients suffer from the less characterized sporadic form of ALS (sALS). As the wobbler mouse and the ALS show striking similarities in view of phenotypical attributes, the mouse is rated as an animal model for the disease. Recent investigations show t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 62 publications
0
19
0
Order By: Relevance
“…Heterozygous animals were used for breeding. Oxidative Medicine and Cellular Longevity spinal cord cell cultures was performed as described before [26]. In brief, homozygous mice were decapitated at the age of p40 and spinal cords were removed.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Heterozygous animals were used for breeding. Oxidative Medicine and Cellular Longevity spinal cord cell cultures was performed as described before [26]. In brief, homozygous mice were decapitated at the age of p40 and spinal cords were removed.…”
Section: Methodsmentioning
confidence: 99%
“…At a cellular level, degeneration of the upper and lower motor neurons, reduced axonal transport, and mitochondrial dysfunction can be observed [24,25]. In the stable stage starting from p40, the symptoms stagnate [26]. Mitochondrial dysfunctions were detected at various time points during wobbler disease.…”
Section: Introductionmentioning
confidence: 99%
“…This prompts not only the search for new therapies, but also for the causes of these ailments more closely. Over the years, caffeine has been investigated as a potential protective or risk factor for psychiatric disorders [ 90 ]. It has already been documented that caffeine intake is associated with depressive symptoms.…”
Section: The Role Of Caffeine In Various Systems In the Human Bodymentioning
confidence: 99%
“…Neurological and psychiatric disorders are not only expensive to treat, but patients have experienced serious stigma, social exclusion, and poor quality of life as a result of their affliction [18]. Over the years, caffeine has been investigated as a potential risk or protective factor for neurological and psychiatric disorders [19]. Some studies have shown that by drinking more than three cups of coffee a day, caffeine reduces the risk of developing AD and PD [20].…”
Section: Introductionmentioning
confidence: 99%